Pengaruh Diskon dan Kualitas Layanan Elektronik terhadap Kepuasan Pelanggan pada Aplikasi Tix ID di Kota Banjarmasin - Nadya Eka Ermida; Saladin Ghalib; Nurul Wahyuni (Smart Business Journal, 2021)
Marketing is all efforts that start from identifying the needs of consumers, determining the right product or service to be marketed, coordinating with other management functions, and developing offers through promotional and distribution strategies. This study aims to determine the effect of discounts and electronic service quality partially and simultaneously on customer satisfaction. Respondents in this study were users of the Tix ID application in Banjarmasin City who were taken using the accidental sampling technique, so that there were 110 respondents who used the Tix ID application as the research sample. Data collection techniques by means of questionnaires and data analysis techniques used are multiple linear regression analysis using SPSS 25.0. The results of this study indicate that partially the discount variable (X1) has no significant effect on customer satisfaction (Y) with a significant value of 0.293> 0.05 with a t value of 1.056 <t table 1.982, and electronic service quality (X2) has a significant effect on customer satisfaction (Y) with a significant value of 0.000 <0.05 with a value of t count 12.080> t table 1.982. Simultaneously, the discount variable (X1) and the quality of electronic services (X2) have a significant effect on customer satisfaction (Y) with a significant value of 0.000 <0.05 with a calculated F value of 84.978> F table 3.08. Keywords: Discounts, Electronic Service Quality, Customer Satisfaction